PENGARUH FREE CASHFLOW, STRUKTUR KEPEMILIKAN, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2012-2013 - Nunuk Mustika Dewi, 10.05.52.0114; Darso, Maryono (Students Journal of Accounting and Banking, 2016)
This research was done because of the phenomenon of the findings of different studies (research gap) on the factors that influence the dividend policy. The aim of research to empirically analyze the effect of free cash flow, ownership structure, profitability and growth of the companys dividend policy. Samples are 49 companies that went public on the Stock Exchange, where the method used is purposive sampling is a sampling method by setting certain criteria, among others: companies listed on the Indonesian Stock Exchange (BEI), dividends and have the data Detailed since 2012-2013, so the pooled method of data (2012-2013), obtained the number of samples (n) = 98. The test results showed that no significant relationship between Free Cashflow, Ownership,Company Growth on policy devidend, there is significant influence and positive relationship between profitability on dividend policy.Keywords: Free Cash Flow, Ownership Structure, Profitability, Growth, Dividend Policy